2020
DOI: 10.3390/ijms21093294
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hemostasis in Chronic Liver Disease and Cirrhosis: What Did We Learn over the Past Decade?

Abstract: Changes in primary hemostasis have been described in patients with chronic liver disease (CLD) and cirrhosis and are still subject to ongoing debate. Thrombocytopenia is common and multifactorial. Numerous studies also reported platelet dysfunction. In spite of these changes, primary hemostasis seems to be balanced. Patients with CLD and cirrhosis can suffer from both hemorrhagic and thrombotic complications. Variceal bleeding is the major hemorrhagic complication and is mainly determined by high portal pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 95 publications
(149 reference statements)
0
15
1
5
Order By: Relevance
“…6,27 As discussed earlier, multiple factors, including potentially reduced thrombin production when platelet counts are <50 × 10 9 /L, 4 contribute to the possibility of increased bleeding risk in CLD patients. [1][2][3] Studies have identified that the risk of procedure-related bleeding is increased when platelet counts fall below approximately 60 to 75 × 10 9 /L, with the highest risk of bleeding occurring when the platelet count is <10 to 20 × 10 9 /L. [28][29][30] In general, CLD patients with platelet counts < − 50 × 10 9 /L are considered to be at high risk for procedurerelated bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,27 As discussed earlier, multiple factors, including potentially reduced thrombin production when platelet counts are <50 × 10 9 /L, 4 contribute to the possibility of increased bleeding risk in CLD patients. [1][2][3] Studies have identified that the risk of procedure-related bleeding is increased when platelet counts fall below approximately 60 to 75 × 10 9 /L, with the highest risk of bleeding occurring when the platelet count is <10 to 20 × 10 9 /L. [28][29][30] In general, CLD patients with platelet counts < − 50 × 10 9 /L are considered to be at high risk for procedurerelated bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thrombocytopaenia associated with chronic liver disease (TCP-CLD) are at risk for both thrombotic and haemorrhagic complications given the complex, altered balance between thrombosis and bleeding in this patient population. [1][2][3] TCP is a reflection of the severity of CLD and contributes to the potential increased risk of bleeding in CLD patients in conjunction with the interplay between multiple elements in the haemostatic system such as platelet dysfunction, anti-platelet antibodies, platelet sequestration and destruction related to hypersplenism, myelosuppression, and alterations in haematopoietic and coagulation factors. [1][2][3] For example, the risk of bleeding in CLD may be affected by decreased thrombin production when platelet counts fall below approximately 50 × 10 9 /L, 4 yet this is countered by an increase in von Willebrand factor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations